1999
DOI: 10.1017/cbo9781107325937
|View full text |Cite
|
Sign up to set email alerts
|

Special Functions

Abstract: Special functions, which include the trigonometric functions, have been used for centuries. Their role in the solution of differential equations was exploited by Newton and Leibniz, and the subject of special functions has been in continuous development ever since. In just the past thirty years several new special functions and applications have been discovered.This treatise presents an overview of the area of special functions, focusing primarily on the hypergeometric functions and the associated hypergeometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
2,671
0
42

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 2,796 publications
(2,735 citation statements)
references
References 0 publications
22
2,671
0
42
Order By: Relevance
“…This leads to the m-tuple integral representation for I (m) similar to the Euler type integral representation for the general plain hypergeometric function m+1 F m ; i.e., I (m) can be interpreted as an elliptic analog of the m+1 F m -function. The recurrence (2.2) is a special realization of an integral analog of the Bailey chains discovered in [18] (the Bailey chains technique is well known as a simplest tool for proving the Rogers-Ramanujan type identities [1]). …”
Section: Continuous Biorthogonal Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This leads to the m-tuple integral representation for I (m) similar to the Euler type integral representation for the general plain hypergeometric function m+1 F m ; i.e., I (m) can be interpreted as an elliptic analog of the m+1 F m -function. The recurrence (2.2) is a special realization of an integral analog of the Bailey chains discovered in [18] (the Bailey chains technique is well known as a simplest tool for proving the Rogers-Ramanujan type identities [1]). …”
Section: Continuous Biorthogonal Functionsmentioning
confidence: 99%
“…. , t 8 ) that generalizes many special functions of hypergeometric type obeying "classical" properties [1]. In particular, it was shown that this function exhibits symmetry transformations tied to the exceptional root system E 7 and satisfies the elliptic hypergeometric equation.…”
Section: §1 Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…To define the Hecke operator T p on S k (X * 6 ) for a prime p relatively prime to 6, we pick an element α in O of norm p and consider the double coset (2), and…”
Section: 4mentioning
confidence: 99%
“…See [5] for an introduction to basic notions and terminology or, for a more detailed account, the monograph [1].…”
Section: Using Classical Hypergeometric Machinerymentioning
confidence: 99%